Review of warm mix rubberized asphalt concrete: Towards a sustainable paving technology. (10th March 2018) - Wang, Haopeng; Liu, Xueyan; Apostolidis, Panos; Scarpas, Tom
Abstract: In recent years, transportation agencies and the general public alike are demanding increased considerations of sustainability in transport infrastructure. Warm mix asphalt (WMA) is developed for reducing energy consumptions and emissions in asphalt paving industry. In addition, the use of rubberized asphalt concrete (RAC) has proven to be economically and environmentally sound and effective in improving the performance of pavements around the world. The combination of WMA and RAC, namely WarmRAC, is a novel and promising paving technology that can realize pavement sustainability from principles to practices. This study summarizes the best practices and recent research findings on warm mix rubberized asphalt concrete, including mix design, construction techniques, performance evaluation, feasibility of recycling, and environmental and economic benefits. Although most research findings to date about WarmRAC are positive, it still has a long way for WarmRAC to be fully adopted worldwide. Therefore, life cycle assessment including environmental and economic impacts, and long-term performance of WarmRAC need further research with involvement of transportation agencies, industry and academia.